The Genesis question scientific advances and the accuracy of Genesis - Ross, Hugh Norman, 1945- (Colorado Springs, CO NavPress, 1998)
Includes bibliographical references and index.
Reprint.
Keywords: Bible and science; Bible. O.T. Genesis I-XI -- criticism, interpretation,etc; Bible. O.T. Genesis I-XI -- evidences, authority, etc